2021
DOI: 10.21125/inted.2021.1605
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stakeholders’ Evaluation on the Quality of Reusable Learning Objects Following the Aspire Participatory Framework

Abstract: As the population is becoming increasingly culturally diverse, there is a growing need for nurses to provide culturally competent care. It has been suggested that health disparities exist within in ethnic minorities and by providing culturally competent care could reduce disparities. The aim of the "TransCoCon: Developing Multimedia Learning for Transcultural Collaboration and Competence in Nursing (GA No 2017-1-UK01-KA203-036612) ERASMUS+ project has been to create innovative accessible multi-media learning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The survey provides a valuable insight into midwifery students' engagement and experiences with interactive online learning and the challenges previously encountered. Our findings reflect that not all midwifery students have experience of online working and for those who have, not all have enjoyed it, resonating with evidence from Ho et al (2021), who found that prior elearning experiences of nursing students were not uniformly positive. Course design, learners' motivation, time management and confidence in using online technologies may affect the success of online learning experiences (Song et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…The survey provides a valuable insight into midwifery students' engagement and experiences with interactive online learning and the challenges previously encountered. Our findings reflect that not all midwifery students have experience of online working and for those who have, not all have enjoyed it, resonating with evidence from Ho et al (2021), who found that prior elearning experiences of nursing students were not uniformly positive. Course design, learners' motivation, time management and confidence in using online technologies may affect the success of online learning experiences (Song et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Detailed specifications are created to describe the resource, such as texts, video scripts, and activity interactions. This iterative process encourages review by a content expert, such as a consultant surgeon, in order to ensure the high quality of the content [31]. This streamline process allows the digital resource to be developed without the need for multiple development rounds or multiple inputs from experts.…”
Section: Design Learning Goals With a Best Practice Frameworkmentioning
confidence: 99%
“…Reusability eliminates the need to create new objects each time, lowering costs and increasing productivity. (Ho, 2021), (Mourão & Netto, 2019) A learning object, according to the International Society for Technology in Education (ISTE), is any digital or non-digital object that supports the learning process and can be customized to the needs of a group of learners and reused in other learning situations. Also, it can define them as "digital learning units that contain small particles of educational content prepared in a digital form, address a specific goal, and can be reused in another educational situation.…”
Section: Concept Of Learning Objectsmentioning
confidence: 99%